The effect of plant-derived peptides on the hot-melt stickiness of herbal extracts during spray drying. Issue 4 (6th March 2023) - Wang, Yan; Shi, Xiaohong; Ren, Wenxia; Wu, Fei; Zhao, Lijie; Du, Ruofei; Lin, Xiao; Wang, Youjie
Abstract: The aim of this study was to explore plant-derived peptides as carrier material with the function of anti-hot-melt stickiness of traditional Chinese herbal extracts during spray drying. Crataegi fructus extract (CFE) with a severe hot-melt stickiness problem was used as a model drug, and soy peptides (SPT) were screened as the most effective and suitable carrier material among seven plant-derived proteins and peptides which include soy protein isolate, walnut protein and five kinds of peptides (corn peptides, wheat peptides, walnut peptides, rice peptides and SPT). The addition of 15% SPT also exhibited a strong anti-stickiness effect in other four hot-melt sticky herbal extracts from Chinese herbs ( Lycii fructus, Corni fructus, Chaenomelis fructus and Mume fructus ) since the obtained powder increased from completely sticking to the wall to more than 50% powder yield. The dynamic surface tensions (DST) of CFE decreased consistently with the increase of SPT from 5% to 20%, and DST1000ms had consistent reduction with the addition of SPT from zero to 20%. Meanwhile, the adhesive force of the single droplet at 28 min decreased below 18.5 N. The softening point of the spray-dried powder of CFE added 15% SPT increased by about 40 °C, and the addition of 15% SPT improved the stability which might be similar with the addition of 50% MD based on scanning electron microscope analysis but more efficiently. These findings confirmed that SPT plant-derived could serve as effective and stable carrier material with good anti-stickiness ability during spray drying.